Treadmill Exercise Attenuates Cerebral Ischemia–Reperfusion Injury by Promoting Activation of M2 Microglia via Upregulation of Interleukin-4 - Lu, Juanjuan; Wang, Jie; Yu, Long; Cui, Rong; Zhang, Ying; Ding, Hanqing; Yan, Guofeng (Frontiers in Cardiovascular Medicine, 2021)
Background: Exercise has been proven to be an effective therapy for stroke by reducing the microglia-initiated proinflammatory response. Few studies, however, have focused on the phenotypic changes in microglia cells caused by exercise training. The present study was designed to evaluate the influence of treadmill exercise on microglia polarization and the molecular mechanisms involved. Methods: Male Sprague-Dawley rats were randomly assigned into 3 groups: sham, MCAO and exercise. The middle cerebral artery occlusion (MCAO) and exercise groups received MCAO surgery and the sham group a sham operation. The exercise group also underwent treadmill exercise after the surgery. These groups were studied after 4 days and 7 days to evaluate behavioral performance using a modified neurological severity score (mNSS), and infarct conditions using 2,3,5-triphenyl tetrazolium chloride. Quantitative real-time polymerase chain reaction (qRT-PCR) and Luminex was employed to determine the expressions of markers of microglia phenotypes. Western blotting was employed to identify the phosphorylation levels of Janus kinase1 (JAK1) and signal transducer and activator of transcription 6 (STAT6). Immunofluorescence was conducted to identify microglia phenotypes. Results: Treadmill exercise was found to improve neurobehavioral outcomes, mainly motor and balance functions, reduce infarct volumes and significantly increase interleukin-4 (IL-4) expression. In addition, treadmill exercise inhibited M1 microglia and promoted M2 microglia activation as evidenced by decreased M1 and increased M2 markers. Furthermore, an obvious increase in p-JAK1 and p-STAT6 was observed in the exercise group. Conclusions: Treadmill exercise ameliorates cerebral ischemia–reperfusion injury by enhancing IL-4 expression to promote M2 microglia polarization, possibly via the JAK1-STAT6 pathway.